Utilizing Baamboozle as Media in teaching Vocabulary Mastery - Vasya, I Dewa Ayu Made Shaffalya; Puspitaloka, Nina; Kartini , Dedeh (Journal of Educational Sciences, 2025)
Vocabulary is a key and very important in deepening English. Many students find it difficult to learn many words because they are bored and stressed. In response to this problem, the use of Baamboozle as media in teaching to help students to have motivated in learning vocabulary mastery. This study aims to find out the implementation of Baamboozle as media in teaching vocabulary and students' responses using Baamboozle as media in learning vocabulary. The research used qualitative method with a case study design. Data was collected through observation and interviews. The participants in this research were grade VIII students from one of the public junior high schools in Karawang. This research found that using Baamboozle as media in teaching vocabulary in junior high school can be beneficial because the game can be adapted to the students' needs with adaptive environment and the students felt enthusiastic and enjoyed the learning process.